The Power of Policy Entrepreneur in Disability- inclusive Policy-Making - Erna Setijaningrum; Ramaditya Rahardian (Indonesian Association for Public Administration, 2022)
This research aims to describe the power of policy entrepreneurs in disability-inclusive policy-making. Disability-inclusive policy in the Jember Regency of East Java, Indonesia, is a result of a thirteen-year- long struggle of the disability groups. Their struggle started as a series of demonstrations, petitions, and hearings with the Regional House of Representatives and the Regent. It then continued with a series of debates and negotiations with the policy-makers. This descriptive- qualitative research utilized Kingdon’s multiple stream framework analysis to capture the stipulation of Regional Regulation Number 7 of 2016 on the Protection and Fulfillment of the Rights of Persons with Disabilities. The informants were six disabled persons and two former members of the Regional House of Representatives. The study finds that the problem stream was raised through demonstrations, petitions, and hearings; the policy stream was done through efforts to include the draft of the disability act in the regional legislative program. Policy windows took place during the momentum initiated by the stipulation of a nationwide disability-inclusive policy by the state government, and, finally, policy entrepreneurs act through lobbies and negotiations. This study concludes that the disability policy-making process in Jember Regency was influenced by the strong power of policy entrepreneurs. Disability groups and the Regional House of Representatives as a policy entrepreneur force acted quickly to take advantage of the open policy window momentum, and, finally, the policy maker ratifies local regulations regarding the protection and fulfillment of the rights of persons with disabilities.